Inaktivasi Termal Spora Eupenicillium javanicum Dalam Jus Nanas - Rizkya Ramadhani; Evelyn Evelyn; Sri Rezeki Muria (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
These days, people's interest in consuming fruit juice such as pineapple in containers is very high because it is easier to consume and has a longer shelf life. Pineapple juice that is not processed properly can be contaminated with various decomposing microorganisms, one of which is the fungus Eupenicillium javanicum. E. javanicum can form spores and cause decay in pineapple which if consumed will cause mycotoxins. Therefore, processing by thermal pasteurization is needed to reduce certain undesirable microorganisms in the fruit juice products. The purpose of this study was to determine the effect of temperatures (80, 85, and 90 ℃ ) and spore age (30 and 60 days) on the thermal inactivation of E. javanicum spores. For 30day-old spores, to reduce 1 log of spores in pineapple juice at 13 ° Brix, it takes 27.62 minutes at 80 ° C, 12.8 minutes at 85 ° C and 3.19 minutes at 90 ° C. Also for the spores with 60 days there was a decrease in logarithms, namely at 43.67 minutes at 80 ° C, 29.07 minutes at 85 ° C and 6.5 minutes at 90 ° C. It was found that the temperature and age of the spores greatly influenced the level of resistance of E. javanicum spores in pineapple juice. Keywords: inactivation, pineapple, resistance, spores, E. javanicum